Formulation of alternative culture media for bacterial and fungal growth - Uthayasooriyan, M.; Pathmanathan, S.; Ravimannan, N.; Sathyaruban, S. (University of Jaffna, 2016)
The microorganisms are grown for many purposes. Culture media used in the laboratory for the cultivation of microorganism supply the nutrients required for the growth and maintenance. Nutrient agar (NA) is universally used as a general purpose medium for the cultivation of broad range of bacteria. Potato Dextrose Agar (PDA) is commonly used for the isolation and growth of wide range of Fungi. The feasibility of developing alternative media to different culture media namely PDA and NA were assessed using locally available cheap materials because the use of readymade culture media in schools and laboratories has financial limitations. Generally the cheap locally available materials such as cereals and legumes may serve as alternative nutrient media to grow bacteria and fungi. The materials used in this study were rice, chickpea, corn, dhal, thinai, natural soy flour and processed soy flour (TVP). For bacteria the test organisms used were E.coli, Pseudomonas sp., Bacillus sp., Staphylococcus sp. and Klebsiella sp. The Klebsiella sp. grows well in all alternative nutrient sources and generally Bacillus sp., grows less in all alternative culture media. The colony morphological characters of bacteria such as shape, margin, elevation and colour were generally similar compared with NA. For fungi the test organisms used were Trichoderma sp., Aspergillus sp., Penicillium sp., Sclerotium sp. and Fusarium sp. On average Sclerotium sp. showed significantly (p<0.05) higher growth in rice. Penicillium sp. showed significantly (p<0.05) low growth in rice and corn. The present study clearly showed in comparison with PDA and NA the possibility of using cheap locally available materials such as rice, chickpea, corn, dhal, thinai, natural soy flour and TVP as alternative nutrient media for bacteriological and mycological studies.
Keywords: Culture media; Alternative nutrient sources; NA; PDA; Bacteria; Fungi